The operating room as a clinical learning environment: An exploratory study. (May 2016) - Meyer, Rhoda; Van Schalkwyk, Susan C.; Prakaschandra, Rosaley
Abstract: Students undertake their clinical placement in various clinical settings for the exposure to and acquisition of skills related to that particular context. The operating room is a context that offers the opportunity to develop critical skills related to the perioperative care of the patient. Despite numerous studies that have been undertaken in this field, few have investigated the operating room as a clinical learning environment in the South African private healthcare context. The aim of this study was to determine nursing students' perceptions of the operating room as a clinical learning environment. An exploratory, interpretive and descriptive design generating qualitative data was utilized. Eight nursing students completed an open-ended questionnaire, and twelve nursing students participated in the focus group discussion. Four themes emerged, namely, 'interpersonal factors', 'educational factors', 'private operating room context', and 'recommendations'. The opinion that the operating room offers an opportunity to gain skills unique to this context was expressed. However, despite the potential learning opportunities, the key findings of this study reveal negative perceptions of nursing students regarding learning experiences in the operating room. Exploration into the preparatory needs of students specific to learning outcomes before operating room placement should be considered. It will also be necessary to improve collaboration between lecturers, mentors and theatre managers. Highlights: Nursing students' perceptions of the operating room as a clinical learning environment is explored. Key findings of this study reveal negative perceptions of students regarding learning experiences in the operating room. Exploration into the preparatory needs of students specific to learning outcomes before placement should be considered. Improving collaboration between lecturers, mentors and theatre managers is also necessary.